Consequences and prospects of the application of Artificial Intelligence to criminal cases - Pedrina, Gustavo Mascarenhas Lacerda (2019)
This article aims to make an analysis of the current application and perspectives of what is popularly known by artificial intelligence to criminal law. Two aspects of machine learning are analyzed: statistical computation and predictive analysis. It discusses the consequences and alternatives for the use of artificial intelligence techniques taken the advances in the brain sciences, some relevant points on the topic are highlighted to promote discussions about future scenarios of this area and possible current applications.